Assessing the effectiveness of interactional feedback for L2 acquisition: Issues and challenges. (January 2020) - Nassaji, Hossein
Abstract: How to correct learner errors has long been of interest to both language teachers and second language acquisition (SLA) researchers. One way of doing so is through interactional feedback, which refers to feedback provided on learners' erroneous utterances during conversational interaction. Various theoretical claims have been made regarding the beneficial effects of interactional feedback, and over the years a considerable body of research has examined its effectiveness. In this context, a central and challenging question has always been how to determine whether such feedback is effective for language learning. Studies investigating the role of feedback have used various measures to assess its usefulness. In this paper, I will begin with a brief overview of the recent studies examining interactional feedback, with a focus on how its effectiveness has been assessed. I will then examine the various measures used in both descriptive and experimental research and discuss the issues associated with such measures. I will conclude with what continues to pose us a challenge in assessing the role of feedback and offer some recommendations to inform future research in this area.